STING signaling in inflammaging: a new target against musculoskeletal diseases - Song, Chenyu; Hu, Zhuoyi; Xu, Dingjun; Bian, Huihui; Lv, Juan; Zhu, Xuanxuan; Zhang, Qiang; Su, Li; Yin, Heng; Lu, Tong; Li, Yinghua (Frontiers in Immunology, 2023)
Stimulator of Interferon Gene (STING) is a critical signaling linker protein that plays a crucial role in the intrinsic immune response, particularly in the cytoplasmic DNA-mediated immune response in both pathogens and hosts. It is also involved in various signaling processes in vivo. The musculoskeletal system provides humans with morphology, support, stability, and movement. However, its aging can result in various diseases and negatively impact people's lives.While many studies have reported that cellular aging is a leading cause of musculoskeletal disorders, it also offers insight into potential treatments. Under pathological conditions, senescent osteoblasts, chondrocytes, myeloid cells, and muscle fibers exhibit persistent senescence-associated secretory phenotype (SASP), metabolic disturbances, and cell cycle arrest, which are closely linked to abnormal STING activation. The accumulation of cytoplasmic DNA due to chromatin escape from the nucleus following DNA damage or telomere shortening activates the cGAS-STING signaling pathway. Moreover, STING activation is also linked to mitochondrial dysfunction, epigenetic modifications, and impaired cytoplasmic DNA degradation. STING activation upregulates SASP and autophagy directly and indirectly promotes cell cycle arrest. Thus, STING may be involved in the onset and development of various age-related musculoskeletal disorders and represents a potential therapeutic target. In recent years, many STING modulators have been developed and used in the study of musculoskeletal disorders. Therefore, this paper summarizes the effects of STING signaling on the musculoskeletal system at the molecular level and current understanding of the mechanisms of endogenous active ligand production and accumulation. We also discuss the relationship between some age-related musculoskeletal disorders and STING, as well as the current status of STING modulator development.